Application of Auto-Regressive Distributed Lag Model (ARDL) Bound Test on Selected Macroeconomic Variables - Chinenye, Amalahu Christian; Acha, Chigozie Kelechi (Universitas Negeri Malang, 2018)
This study examined the application of Auto-regressive distributed lag model (ARDL) bound test on some selected macroeconomic variables spanning from 1981-2017 obtained from the statistical Bulletin of Central Bank of Nigeria (CBN). The data were analyzed using the E-views 9.0 software. F-statistic of 5.9167 was found to be higher than the critical value of 3.79 in the Lower Bound I(0) and 4.85 in the Upper bound I(1) at the 5 % level, thus null hypothesis was rejected. ARDL (1, 2, 0) was found to be the best fit model for showing a long-run and short-run relationship between Gross Domestic Product (GDP), Exchange rate, and Interest rate. There is a long-run relationship among GDP, Exchange rate, and Interest rate which means that the variables under study are co-integrated. Also, a unidirectional relationship running from exchange rate to GDP exist. The study recommends the use of supportive fiscal and monetary policies that will tighten the local currency market and provide a set of incentives aimed at removing anti-export bias barriers so as to promote exports and boost GDP, particularly non-oil exports and discourage import of consumer goods to stabilize the exchange rate. Keywords: ARDL Bound test; Gross Domestic Product; Exchange rate; Macroeconomic Variables; Interest rate.JEL Codes: E06; O2; O4